2022
DOI: 10.14814/phy2.15245
|View full text |Cite
|
Sign up to set email alerts
|

The effect of brain serotonin deficiency on breathing is magnified by age

Abstract: Serotonin is an important mediator modulating behavior, metabolism, sleep, control of breathing, and upper airway function, but the role of aging in serotoninmediated effects has not been previously defined. Our study aimed to examine the effect of brain serotonin deficiency on breathing during sleep and metabolism in younger and older mice. We measured breathing during sleep, hypercapnic ventilatory response (HCVR), CO 2 production (VCO 2 ), and O 2 consumption (VO 2 ) in 16-18-week old and 40-44-week old mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…We found that, regardless of age, brain-5-HT-deficient mice exhibited suppressed control of breathing during NREM and REM sleep. During wakefulness, 16-18-week-old mice with brain 5-HT deficiency maintained ventilation and hypercapnic ventilatory response during hypercapnia, whereas older 40-44-week-old 5-HT-deficient mice had decreased ventilation and hypercapnic ventilatory responses [119]. These data suggest that 5-HT plays a role in the neural control of breathing during sleep, which is magnified with aging.…”
Section: Anatomy and Function Of The Raphe Nucleimentioning
confidence: 83%
“…We found that, regardless of age, brain-5-HT-deficient mice exhibited suppressed control of breathing during NREM and REM sleep. During wakefulness, 16-18-week-old mice with brain 5-HT deficiency maintained ventilation and hypercapnic ventilatory response during hypercapnia, whereas older 40-44-week-old 5-HT-deficient mice had decreased ventilation and hypercapnic ventilatory responses [119]. These data suggest that 5-HT plays a role in the neural control of breathing during sleep, which is magnified with aging.…”
Section: Anatomy and Function Of The Raphe Nucleimentioning
confidence: 83%
“…Sixth, we only assessed trueV̇O2${\dot V_{{{\rm{O}}_{\rm{2}}}}}$ and trueV̇CnormalO2${\dot V_{{\rm{C}}{{\rm{O}}_{\rm{2}}}}}$ under normoxia. Metabolic measurements using CLAMS units are only validated under room air conditions (Pho et al., 2021, 2022). Further studies regarding the effects of TRPM7 in the CB on respiratory metabolism in response to hypoxia are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Ventilatory response to hypercapnia (HCVR) during wakefulness was assessed at baseline and after 9−10 days of Trpm7 shRNA expression in the CB area as previously reported by our group (Pho et al., 2022). Measurements were performed using a similar design as the HVR protocol.…”
Section: Methodsmentioning
confidence: 99%
“…We measured apnea index across sleep stages in accordance with our previous study. 96 Apneas were scored as ≥ 90% reduction in airflow for a period corresponding to two or more breath cycles or ≥0.7 s based on average respiratory rate at baseline.…”
Section: Methodsmentioning
confidence: 99%
“…Metabolic studies were performed as previously described. 47 , 96 Mice were placed in individual Comprehensive Laboratory Animal Monitoring System (CLAMS) units (Oxymax series; Columbus Instruments, Columbus, OH) for a 24-h acclimation period followed by 24 h of continuous recordings starting at 10:00a.m. The CLAMS units were sealed and equipped with O 2 electrochemical sensors, CO 2 infrared sensors and infrared beam movement sensors.…”
Section: Methodsmentioning
confidence: 99%